(untitled) (Clinics, 2010)
INTRODUCTION: There is little data concerning the ability of Eurycoma longifolia Jack (EL) to reverse the inhibitory effects of estrogen on testosterone production and spermatogenesis. The aim of the present study was to determine the effect of EL on testicular histology and sperm count in estrogen-treated male rats. METHODS: Adult male Sprague-Dawley rats weighing 200-250 g were divided into four groups of six rats each. Group A (control) was given solvent in the same manner as the treated groups were given EL. Group B was treated with EL (8 mg/kg body weight) orally. Group C was treated with estradiol (E2) (intramuscular dose of 500 μg/kg body weight), and group D received a combined treatment of oral EL and intramuscular E2. After fourteen consecutive days of treatment, rats from all groups were sacrificed and subjected to spermatogenic and epididymal sperm cell counts. RESULTS: The spermatogenic cell count in the E2-treated group was significantly decreased as compared to the control (p < 0.05) and EL+E2-treated groups (p < 0.05). A similar finding was found for the epididymal sperm count; the E2-treated group had a significant decrease in the count compared to the control (p < 0.05) and EL+E2-treated groups (p < 0.05). Rats that were treated with EL alone exhibited significantly higher sperm counts and sperm motility when compared to the control group (p < 0.05). CONCLUSIONS: EL extract acts as a potential agent for reversing the effects of estrogen by increasing spermatogenesis and sperm counts in rats after fourteen consecutive days of treatment.